Intimate partner violence exposure and self-regulation in children and adolescents: a systematic review - Zhang, Ying (Journal of family violence, 2025)
Purpose: Millions of U.S. households have children who have witnessed intimate partner violence (IPV) between their caregivers. The far-reaching negative influences of IPV on children encompass numerous psychological outcomes and delays in various domains of child development. Given the critical role of self-regulation in cognitive and social functioning, which is necessary for navigating complex social situations and academic success, investigating the impact of IPV on its development is of particular importance. Thus, the objective of this study is to conduct a systematic review of empirical research examining the relationship between IPV exposure and the development of children’s self-regulation. Methods: This study systematically reviewed 13 peer-reviewed studies published between 2000 and 2021 that quantitatively examined the effects of IPV exposure on self-regulation in children and adolescents. Studies were found using selected keywords across four scientific databases. Results: Among the 13 studies included in the review, 10 studies identified significant negative effects of IPV exposure on various aspects of self-regulation (i.e., emotional regulation, executive function, and behavioral regulation), and two studies identified indirect pathways through parenting and maternal depression. Conclusions: Previous studies indicate that the normal development of self-regulation in children may be disrupted by stressful and conflict-ridden home environments. Further research is necessary to explore the mechanisms and timing by which IPV exposure influences the development of self-regulation in children, as well as protective factors that may mitigate IPV’s negative effects.